The importance of human resources transformation (HRT) project: Case study Algerian company (Sonatrach) plan 2023 - Madani, Touihar Taha (The International tax journal, 2025)
This study aims to explore the important and strategic topic of human resource transformation through a case study of the Algerian oil &gas company Sonatrach, which began implementing its human resource transformation project in 2020 and is still on its way to fully implementing it, this study relied on official periodic and annual reports and documents for the year 2023, this study reached a set of results, the most important of which are: Sonatrach is increasing the number of employees and giving great importance to the training process in order to make its project a success. This study concluded with a set of recommendations, including the need to expand the categories participating in training operations and to work to enrich the latter.